Efficacy of Coating Materials on Urea Applied Under Saline Water Irrigation. I. Mineralization of Urea-N - Mago, G S; Totawat, K L (Annals of Arid Zone, 2016)
Efficacy of indigenous coa ting materials for urea under saline water irrigation was assessed by incubation for 21 days. Different coating materials definitely affected mineralization of applied urea. The formation of urea-N and NH4-N decreased and the formation of NO3-N increased as the period of incubation advanced be)'ond three days. However, higher values of urea- N and NH4-N and lower values of NO3-N were recorded in the soil receiving urea coated with neem (Azadirachta indica) and mahua (Bassia latifolia) cakes (300 g cake kg_1 urea) in conjunction with coaltar, Under these treatments the nitrification rate remained low and the per cent inhibitiod in nitrification of applied urea remained high when examined beyond one day of incubation period. Efficiency of inhibition of nitrification was in the order 'neem' cake> 'mahua cak: > sulphur> gypsum> coaltar.